Enseignement de la géométrie à des élèves dyspraxiques visuospatiaux inclus en classe ordinaire - Édith Petitfour (Recherches en Éducation)
Teaching methods of geometry, which are based on the construction with instruments - ruler, square, pair of compasses - and on a sharp perception of figures, lead a pupil with visual spatial dyspraxia to failure. From our observations of ten pupils with visual spatial dyspraxia included in ordinary class during geometry lessons, in grades 5th and 6th, we first present the difficulties and obstacles to which they are confronted, and which hinder them in their school learning. Then, we try to determine whether resorting to a numerical environment should help improve these pupils’ learning abilities. Finally, we analyse different types of help brought to these pupils in different schemes of work in a paper-pencil environment, in order to find out those that could be judicious to help them to progress.